Measurement of angular parameters from the decay B-0 -> K*(0)mu(+)mu(-) in proton-proton collisions at root s=8 TeV - (:unkn) unknown (ELSEVIER, 2018)
Angular distributions of the decay B-0 -> K*(0)mu(+)mu(-) are studied using a sample of proton-proton collisions at root s = 8 TeV collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 20.5 fb(-1). An angular analysis is performed to determine the P-1 and P-5' parameters, where the P-5' parameter is of particular interest because of recent measurements that indicate a potential discrepancy with the standard model predictions. Based on a sample of 1397 signal events, the P-1 and P-5' parameters are determined as a function of the dimuon invariant mass squared. The measurements are in agreement with predictions based on the standard model. (C) 2018 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Physics; B-0 decays; MODEL-INDEPENDENT ANALYSIS; SUPERSYMMETRIC THEORIES; PHYSICS